2008
DOI: 10.1038/nn.2218
|View full text |Cite
|
Sign up to set email alerts
|

Feedback of visual object information to foveal retinotopic cortex

Abstract: The mammalian visual system contains an extensive web of feedback connections projecting from “higher” cortical areas to “lower” areas including primary visual cortex. Although multiple theories have been proposed, the role of these connections in perceptual processing is not understood. Here we report a surprising new phenomenon not predicted by prior theories of feedback: the pattern of fMRI response in human foveal retinotopic cortex contains information about objects presented in the periphery, far away fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
232
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(260 citation statements)
references
References 36 publications
27
232
1
Order By: Relevance
“…More recent work indicates that nonstimulated regions of V1 contain information about stimuli presented elsewhere in the visual field and that they receive this information via corticocortical top-down (rather than lateral) projections. 69,70 Early visual cortices also encode information about stimuli presented in modalities other than the visual, 71,72 and analogous findings exist for the early auditory 71,73 and somatosensory 71,74 cortices. All of these findings indicate that top-down signals can induce, in their target areas, activity patterns of considerable resolution.…”
Section: Top-down Signals and Conscious Perception: What We Already Knowmentioning
confidence: 60%
“…More recent work indicates that nonstimulated regions of V1 contain information about stimuli presented elsewhere in the visual field and that they receive this information via corticocortical top-down (rather than lateral) projections. 69,70 Early visual cortices also encode information about stimuli presented in modalities other than the visual, 71,72 and analogous findings exist for the early auditory 71,73 and somatosensory 71,74 cortices. All of these findings indicate that top-down signals can induce, in their target areas, activity patterns of considerable resolution.…”
Section: Top-down Signals and Conscious Perception: What We Already Knowmentioning
confidence: 60%
“…These differences may have arisen from variations in (i) measurement methodology (traveling wave vs. pRF modeling), (ii) signal-to-noise ratios, and (iii) effects arising from the stimulus types, such as perceptual filling in. Our moving bar stimulus, for example, likely produced a greater effect of filling in, which might be reflected in top-down influences producing activity in foveal V2, V3, hV4, and VO-1 (19,47). Along these lines, a recent study by Williams et al (19) showed that feedback from higher cortical areas can produce differential effects in the fovea vs. the periphery of early visual cortex.…”
Section: Comparisons With Studies On the Cortical Effects Of Other Rementioning
confidence: 83%
“…Third, it is expected that neurons with RFs partially eclipsed by the SPZ may show a scaling of their RF sizes, although whether these increase or decrease in size is difficult to predict. Such neurons' new RF spans will necessarily be reduced by the overlap with the SPZ, but their RF sizes may also be increased because of changes in feedback activity or a reduction in lateral inhibitory connections to nearby neurons that have also been silenced or shifted to ectopic locations by the scotoma (1,2,(17)(18)(19)(20). The combination of these effects could also lead to no observable change at this level of measurement.…”
Section: Significancementioning
confidence: 99%
“…Instead, active predictions about upcoming sensory events continuously influence the incoming signal and interact as top-down projections with earliest perceptual processes (Bar, 2007;Carlsson, Petrovic, Skare, Petersson, & Ingvar, 2000;Churchland et al, 1994;Corbetta & Shulman, 2002;Engel, Fries, & Singer, 2001;Enns & Lleras, 2008;Gilbert & Sigman, 2007;Kastner, Pinsk, De Weerd, Desimone, & Ungerleider, 1999;Kutas, 2006;Kveraga, Ghuman, & Bar, 2007;McClelland & Rumelhart, 1981;Mechelli, Price, Friston, & Ishai, 2004;O'Connor, Fukui, Pinsk, & Kastner, 2002;Somers, Dale, Seiffert, & Tootell, 1999;Williams, Baker, Op de Beeck, Mok Shim, Dang, Triantafyllou et al, 2008).…”
Section: Predictability: Top-down Expectationsmentioning
confidence: 99%